Effect of Job Security and Governance on Teacher’s Job Satisfactions of Higher Educational Institutions in Southern Punjab - Saif, Amir; Adnan, Muhammad (Information Management and Business Review, 2019)
Educational institutes in Pakistan have become progressively successful. In the last few decades Pakistan is facing tremendous challenges particularly in education and due to insufficient and ineffective public education system. However, there is need to plan and strategize upcoming challenges bases on education machinery workforce placement, capability and capacity. This study is aiming to examine the relationship between, job security, governance, and teacher’s job satisfaction. In addition this study is also investigating the moderating effect of leadership style between job security and governance. This study has used SMART-PLS structural equation modeling to analyze the data using quantitative research method. This study has used quantitative research method using stratified sampling technique. This study had used 266 completed and usable questionnaires collected from teacher of the institutions in Sothern Punjab- Pakistan. The findings have indicated a significant relationship between job security, governance and job satisfaction at educational institution level. In addition it was also reveals that leadership style has no significant influence between job security, governance and teacher’s job satisfaction. The influence of these factors calls for the further research. There is also need to carry out a similar but comparative study in rural settings.